POLA PENANGGULANGAN KERUSAKAN LINGKUNGAN EFEK EKSPLORASI DAN PRODUKSI TAMBANG NIKEL PT. SAMBAS MINERALS MINING DAN PT. MACIKA MADA MADANA (Studi Kasus: Kec. Palangga Selatan, Kab. Konawe Selatan) - Adenisatrawan Adenisatrawan; Yogi Indra Yadin (Institut Agama Islam Negeri (IAIN) Kendari, 2019)
In this paper describes the pattern of environmental damage mitigation effects of nickel mining exploration and production PT. Sambas Minerals Mining and PT. Macika Mada Madana in South Palangga District, Konawe Selatan District. The research objective is to describe the effects of nickel mining exploration and production effects, damage control patterns, how to ensure damage to the target is right or not, and sustainable environmental damage management patterns. This type of research is a qualitative method with a descriptive approach. Qualitative studies pay attention to processes, events, and authenticity. The type of data used in this study is primary data which is data obtained directly from the first sources. The unit of analysis is the people of the South Palangga District and the community. The researcher used a purposive technique in selecting informants. The informants were the village head and the head of farmer groups and fishermen in South Palangga District, the seat manager/summit of the mining company and the Head of the Konawe Selatan Mining Office. Data collection techniques are structured interviews, participatory observation. Steps for analyzing data obtained in the field are recorded or recorded in narrative form. Then data reduction, selection and concentration processes. The final step is drawing conclusions and verification. From the results of the study concluded, the effects of mining exploration and production give rise, high flood volumes in each rainy season come, siltation of rivers, sandy rice fields, decreasing volume of well water, increasing pests of pigs and monkeys due to increasingly narrow forests, cattle feed space increasingly narrow, especially in the coastal communities seaweed farmers stopped completely, and the fishermen looking for fish were getting farther away, as well as erosion and sedimentation. replacement of land losses, royalty, watering, making pond sediments, closing former extraction of material ore/nickel and reclamation and reforestation and the construction of community facilities and infrastructure, such as the manufacture of dug and fertile drill wells. To ensure effective prevention by prioritizing the principles of transparency and accountability, as well as overcoming sustainable environmental damage through post-mining reclamation and afforestation.